DERMATOSCOPY AS A METHOD OF EVALUATING THE EFFICIENCY OF 5% CREAM IMYKVIMOD IN PATIENTS WITH BASAL CELL CARCINOMA OF SKIN - M. V. Zhuchkov; D. B. Sonin; M. A. Tarasova; S. A. Kosorukova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The aim. investigation of the possibilities of dermatoscopy as a method for evaluating the effectiveness of therapy with topical imiquimod in patients with superficial basal cell carcinoma (CCB). Materials and methods. the study included 24 patients with a superficial form of CCB, who for various reasons did not undergo excisional surgical intervention and who agreed to alternative drug therapy (officinal original topical imiquimod). Patients were divided into two groups, in which the efficacy of therapy was assessed either by clinical or by dermatoscopic signs. General results. the study demonstrated the importance of dermatoscopy as a method for assessing the effectiveness of therapy with topical imiquimod; Greater prognostic significance of dermatoscopy in comparison with a simple clinical examination of mass when assessing the moment of interruption of drug therapy with imiquimod.